2022
DOI: 10.3390/ijms231810313
|View full text |Cite
|
Sign up to set email alerts
|

Indications of Peripheral Pain, Dermal Hypersensitivity, and Neurogenic Inflammation in Patients with Lipedema

Abstract: Lipedema is a disease with abnormally increased adipose tissue deposition and distribution. Pain sensations have been described in the clinical evaluation of lipedema, but its etiology remains poorly understood. We hypothesized that pain sensitivity measurements and ex vivo quantitation of neuronal cell body distribution in the skin would be lipedema stage-dependent, and could, thus, serve to objectively characterize neuropathic pain in lipedema. The pain was assessed by questionnaire and peripheral cutaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 32 publications
(49 reference statements)
0
13
3
2
Order By: Relevance
“…tended to be increased compared to controls, but was not significantly different. However, LiDo patients were significantly more sensitive on the calf and arm than the controls [31]. One problematic aspect of this study, however, is that only 3 out of 5 patients in stage I reported any pain at all and only 8 out of 13 patients in stage II; only the 16 patients in stage III reported consistent pain.…”
Section: Painmentioning
confidence: 60%
See 4 more Smart Citations
“…tended to be increased compared to controls, but was not significantly different. However, LiDo patients were significantly more sensitive on the calf and arm than the controls [31]. One problematic aspect of this study, however, is that only 3 out of 5 patients in stage I reported any pain at all and only 8 out of 13 patients in stage II; only the 16 patients in stage III reported consistent pain.…”
Section: Painmentioning
confidence: 60%
“…The etiology of peripheral neuropathy involves reduced intradermal neuronal density [32,33]. The authors counted the number of Tuj1-positive cell bodies per skin length from thigh tissue biopsies and found no difference in density between control and LiDo samples; surprisingly, there were also no differences in cell body density between LiDo stages [31]. This finding actually contradicts neuropathic pain.…”
Section: Painmentioning
confidence: 99%
See 3 more Smart Citations